Doa Batin: Doa Persahabatan Dengan Yesus Menurut Santa Teresia Dari Yesus - Berthold Anton Pareira (Sekolah Tinggi Widya Sasana, 2020)
This is a short study of mental prayer according to St. Teresa of Jesus, doctor of the Church. Mental prayer according to her ‘is nothing else than an intimate sharing between friends to be alone with Him who we know loves us’. This definition is biblical and ahead of Dei Verbum, art.2. God is our friend. Mental Prayer has to be the soul of vocal prayer. Both are closely related as appear in the teaching of Jesus on the persistence of prayer (Lk 11:1-4,5-8,9-13).